2021
DOI: 10.2106/jbjs.21.00301
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Open Approach to Medial Pinning in Pediatric Supracondylar Humeral Fractures May Be Safer Than Previously Thought

Abstract: Background: Displaced pediatric supracondylar humeral fractures (SCHFs) are stabilized after reduction by smooth pins. Although some SCHFs are biomechanically stable after lateral-only entry pinning (lateral pinning), an additional medial entry pin (cross-pinning) confers superior stabilization in some SCHFs. There is a recognized risk of iatrogenic ulnar nerve injury with medial entry pinning. The best existing evidence has estimated an iatrogenic ulnar nerve injury rate of approximately 3.4% in cross-pinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In these future studies, results that need to be reported should include: (a) A clear distinction between acute iatrogenic ulnar nerve injury (motor and sensory loss) and iatrogenic ulnar nerve impingement or irritation (sensory change) because of their very different clinical consequences. 4 (b) Timing to detection and management of the ulnar nerve palsy including time to removal of the medial wire and/or exploration. (c) Findings at surgical exploration. (d) Other complications such as loss of reduction. (e) Detailed clinical recovery at final follow-up. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these future studies, results that need to be reported should include: (a) A clear distinction between acute iatrogenic ulnar nerve injury (motor and sensory loss) and iatrogenic ulnar nerve impingement or irritation (sensory change) because of their very different clinical consequences. 4 (b) Timing to detection and management of the ulnar nerve palsy including time to removal of the medial wire and/or exploration. (c) Findings at surgical exploration. (d) Other complications such as loss of reduction. (e) Detailed clinical recovery at final follow-up. …”
Section: Discussionmentioning
confidence: 99%
“…Of those who had early intervention, 4 (15.4% of the exposure group) did not fully recover at final follow-up. These data came from 2 papers, 4 , 10 and due to the very low numbers and heterogeneity of the data, no statistics could be applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations